Experimental, numerical and analytical investigation of the polyamide 12 powder bed fusion with the aim of building dimensionless characteristic numbers. (March 2021) - Grünewald, Moritz; Popp, Kevin; Rudloff, Johannes; Lang, Marieluise; Sommereyns, Alexander; Schmidt, Michael; Mohseni-Mofidi, Shoya; Bierwisch, Claas
Abstract: In powder bed fusion (PBF), a laser based energy source selectively fuses polymer powder particles in a layer-by-layer process building up a three-dimensional structure. For powder bed fusion of polymers the knowledge about which material properties are important for the process and the product quality is insufficient. This causes significant difficulties in developing new materials. To address this problem, it is necessary to establish a clear link between the material properties, process parameters and the resulting component quality. This link can be achieved by performing a combination of experimental investigations, numerical simulations and analytical considerations to develop dimensionless characteristic numbers that are able to describe the process. Therefore, this paper presents material properties and monolayer printing experiments for polyamide 12. The experimental results are compared with numerical simulations based on the material and process data. Based on these results, we present a method of how to calculate the dimensionless energy input by combining the surface energy density with material properties and measured thickness of the monolayer samples. Furthermore, when considering the fusion time, numerical simulations show good correlation with an analytical model Graphical abstract: Unlabelled Image Highlights: Simulations show that the distribution of thermal energy in the powder bed takes place at the scale of microseconds. Surface temperatures of monolayers differs only for less than 5 °C after 2 s while increasing energy input. Analytical estimations and simulations show that polymer densification is in order of several seconds due to high viscosity Dimensionless energy input correlates well with the absorption level of the polymer. The maximum monolayer thickness measured with a dial gauge is proportional to the introduced laser surface energy density.